Handbook of Oriental studies = Handbuch der Orientalistik / section 4 China / edited by Stephen F. Teiser, Martin Kern, Timothy Brook, Paul W. Kroll volume 37 Handbook of divination and prognostication in China / edited by Michael Lackner, Zhao Lu part 1 Introduction to the field of Chinese prognostication - Lackner, Michael; Zhao, Lu; Teiser, Stephen F.; Kern, Martin; Brook, Timothy; Kroll, Paul W. (Handbook of Oriental studies = Handbuch der Orientalistik, 2022)
"This is the first comprehensive book that presents the manifold aspects of divination and prognostication in traditional and modern China, from the early period of oracle bones to present-day fortune-tellers. It introduces what is out there in the field of Chinese divination and prognostication, and how we can further explore it especially through different disciplines. Eminent specialists outline the classifications of divination, recently excavated texts, the relationship between practitioners and clients, the place of the "occult" arts in cosmology, literature and religion, and the bureaucratic system. Contributors are: Constance Cook, Richard J. Smith, Marc Kalinowski, Stephen R. Bokenkamp, Lü Lingfeng, Liao Hsien-huei, Philip Clart, Fabrizio Pregadio, Esther-Maria Guggenmos, Andrew Schonebaum, and Stéphanie Homola"--